ABM Clinical Protocol #19: Breastfeeding Promotion in the Prenatal Setting, Revision 2015 - Rosen-Carole, Casey (Breastfeed Med, 2015)
A central goal of the Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient.